International conference “Tatarstan – Japan: History and Perspectives of Relations” (Kazan, July 23–24, 2018) - M.M. Gibatdinov (Золотоордынское обозрение)
The Third international Conference “Tatarstan – Japan: History and Perspectives of Relations” was the result of international research cooperation between the Marjani Institute of History and Institute for North East Asian Research (NEAR) of the University of Shimane and was held in Kazan as the part of official program of the Year of Japan in Russia. Among the traditional topics of conference: the cultural contacts between Tatarstan and Japan, the history of Tatar migration in the Far East, the role of Tatars in the dialogue between Japan and Muslims, the promotion of Islam in Japan, ancient metallurgy and “Tatara” steel casting technology, along with ancient and medieval sources about Tatars. This year, the agenda of conference was enlarged by analyses of bilateral business cooperation, and such new topics as the role of Kazan as the center of Orthodox missionary activity in the Orient (translation of sacred texts to the Japanese and Chinese languages, proselytizing activity and the impact of Russian missioners on the development of Sinology and Japanology in Russia, etc.).